1993
DOI: 10.1001/archsurg.1993.01420220063008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Experience With Pancreatic Islet-Cell Tumors

Abstract: This experience from a single institution underscores the role of preoperative localization studies and appropriate surgical management of these rare tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…The outcome of surgery for PNETs has been shown to be significantly better than that for other forms of pancreatic malignancies [73,74] . Table 8 lists the outcomes of surgical treatment (with curative intent) for PNETs reported by a number of institutions worldwide [2,69,70,[73][74][75][76][77][78][79][80][81][82] . The ubiquitous finding in all these studies is that curative resection is associated with excellent long-term survival and symptom control.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…The outcome of surgery for PNETs has been shown to be significantly better than that for other forms of pancreatic malignancies [73,74] . Table 8 lists the outcomes of surgical treatment (with curative intent) for PNETs reported by a number of institutions worldwide [2,69,70,[73][74][75][76][77][78][79][80][81][82] . The ubiquitous finding in all these studies is that curative resection is associated with excellent long-term survival and symptom control.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…A previous study (14) reported that the most frequent preoperative diagnosis of patients with nonfunctioning pancreatic NET was pancreatic cancer, because clinical presentations and CT findings of the pancreatic tumor mimic ductal adenocarcinoma of the pancreas. Similarly, based on the findings of contrast-enhanced CT, we speculated that this patient had pancreatic cancer with multiple liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…For benign pancreatic tumors, enucleation is the first choice, although which is not always possible due to tumor size or localization [1,2]. Pancreaticoduodenectomy, with or without pylorus preservation, is frequently used in the patients with benign tumors confined to the pancreatic head.…”
Section: Introductionmentioning
confidence: 99%
“…A pancreaticoduodenectomy or distal pancreatectomy is the customary treatment for those tumors [1][2][3][4][5][6]. But these two operations are extremely cruel for benign lesions and usually carry important operative complications and potential mortality, and furthermore imply a significant waste of normal pancreatic tissue with the risk of diabetes, exocrine insufficiency, thrombosis and severe infection [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation